The use of relaxation techniques in a clinic of psychology - Blanco, Carmen; Estupiñá, Francisco J.; Labrador, Francisco J.; Fernández-Arias, Ignacio; Bernardo-de-Quirós, Mónica; Gómez, Laura (Anales de Psicología / Annals of Psychology, 2014)
The aim of this study is to identify the use of relaxation techniques (RT) in a clinical context. It presents a general analysis of all relaxation techniques and its frequency of use. It is included a specific analysis depending on the diagnosis and its relationship with the results of the treatment in a sample of 880 patients from the Complutense University Clinic of Psychology. The average age is 32.79 years old, 67.2% are women, and there is almost every kind of diagnosis. The results show that RT have been used in 70.5% of the cases, and the Breathing training was the most used (72.3%). RT are used particularly on anxiety disorders (87.8%), somatoform disorders (84.2%) and impulse control disorders (77.8%). Also the results showed that RT were used more in patients with comorbid disorders (82.4% versus 68%). Patients who used Progressive Relaxation training and Breathing training had similar percentages of discharges, around 69%, compared with non relaxation training 58.1%.The benefits of using RT are discussed and its use in different psychological disorders.